Destiny and Work Ethos as a Degree Strategy: Study in Vocational Community Katangka District Gowa - Mahmuddin Mahmuddin (Proceedings of International Conference on Da'wa and Communication, 2019)
Destiny and work ethic as a Da'wa strategy for the community in the Katangka Village, Gowa Regency. The problem is then broken down into several questions, namely: (1) What is the community's understanding of destiny in the Katangka Kelurahan, Gowa Regency? (2) Can the understanding of destiny encourage the work ethic of the community as a preaching strategy in the Katangka Kelurahan, Gowa Regency? This type of research is classified as qualitative with the research approach used is the sociological approach. The data source of this research is the community in Katangka Village, Gowa Regency. Data collection methods used were observation, interviews, questionnaires and documentation. Data processing and analysis techniques are carried out through three stages namely data reduction, data presentation and conclusion drawing. The results showed that people really believe in the destiny that was set by God from the beginning. The Katangka Kelurahan community understands it as a destiny of the provision of God that cannot be contested, there is also a destiny that requires an effort to change it and there is a destiny that can be known after that event occurs or known as destiny in human perspective. The community's view of destiny can encourage the community's work ethic as part of the Da'wa strategy it is said that destiny is a belief that comes from God and with that destiny the community is driven to seek that destiny by strengthening or doing hard work called the work ethic. Based on this research, the implications of the research are stated that the community should strengthen confidence in the provisions of God so that one continues to strive and work hard to achieve prosperity and meet their needs as part of the Da'wa strategy.